Effect of Aluminium Plate Layers and Electric Current on Pendulum Damping Time - Mahfudz, Khawarizmy; Pramudya, Yudhiakto (Universitas Islam Negeri Ar-Raniry, 2025)
The pendulum is a classic oscillatory system commonly used in physics to study motion and damping phenomena. One notable damping mechanism is electromagnetic damping caused by eddy current induction. This study investigates the effects of varying the number of aluminium plate layers attached to the pendulum and the electric current supplied to a surrounding coil, which generates a magnetic field, on the pendulum damping time. An experimental approach was used by measuring the damping time across different combinations of plate layers and current levels. The data were analyzed to identify the relationship between these variables and the damping behavior of the pendulum. Results indicate a negative exponential relationship between the electric current and damping time, as well as a significant effect of aluminium plate layers on damping efficiency. Increasing the number of aluminium plate layers enhances eddy current induction, resulting in stronger damping forces.